Open Social Scholarship Annotated Bibliography. Issue 1 (30th July 2019) - El Khatib, Randa; Seatter, Lindsey; El Hajj, Tracey; Leibel, Conrad; Arbuckle, Alyssa; Siemens, Ray; Winter, Caroline; ,
This annotated bibliography responds to and contextualizes the growing 'Open' movements and recent institutional reorientation towards social, public-facing scholarship. The aim of this document is to present a working definition of open social scholarship through the aggregation and summation of critical resources in the field. Our work surveys foundational publications, innovative research projects, and global organizations that enact the theories and practices of open social scholarship. The bibliography builds on the knowledge creation principles outlined in previous research by broadening the focus beyond conventional academic spaces and reinvigorating central, defining themes with recently published research.